The karyotype of Blarinomys breviceps (Mammalia: Rodentia: Cricetidae) with comments on its morphology and some ecological notes - Geise, Lena; Bergallo, Helena G.; Esbérard, Carlos E. L.; Rocha, Carlos F. D.; van Sluys, Monique (Zootaxa, 2008)
The geographic distribution of Blarinomys breviceps (Winge) includes few localities in forested areas in the Atlantic Rainforest from Bahia state in Brazil up to Misiones province in Argentina. Here we add 14 new records for the species in the region of southeastern Brazil. These findings provided information on morphology, natural history and the first karyological data for the species. During two short surveys, one in Santuário da Serra da Concórdia, Valença municipality and another in Fazenda Marimbondo, Mauá municipality, Rio de Janeiro State, Brazil, six specimens were collected in pit fall traps. The specimen trapped in Serra da Concórdia was a sub adult male (age class 3 according to the upper molar row wear). In Fazenda Marimbondo, four adult males and one adult female were captured. Serra da Concórdia is a secondary vegetation in a semideciduous forest type, being a small fragment of 220 ha. The second locality, Fazenda Marimbondo is a high montane forest in an evergreen forest type. Karyotype of the specimen collected in the first locality presented a diploid number of 28 chromosomes and an autosomal number of 50. The specimen collected in Serra da Concórdia was kept alive for seven days. During this period it was fed with live arthropods, what confirms their insectivorous feeding habit, consistent with the molar teeth morphology.